Another one goes tonight : a Peter Diamond investigation - Lovesey, Peter (Lovesey, Peter. Peter Diamond mystery., 2016)
"Two police officers are about to head home after a long night shift when they receive one last call: a suspicious nude person has been spotted in the wee hours of the morning. En route to the call, the patrol car spins off the road, killing one of the exhausted cops instantly and leaving the other in critical condition. Whenever a police car is involved in an accident, the matter must be taken very seriously. Inspector Peter Diamond is assigned to look into the case. His supervisor is desperately hoping Diamond will not discover that the car was speeding or that the driver was under the influence of drugs or alcohol--that would make the police look very bad indeed. Instead, Diamond discovers something even worse--a civilian on a motorized tricycle was involved in the crash, and has been lying on the side of the road by the accident for hours undiscovered. Diamond administers CPR, but no one can say whether the man will pull through. If a civilian has been killed by a police vehicle, the department has very big problems on its hands. Meanwhile, Diamond has become suspicious of the civilian victim, and begins a private inquiry. Why was he out in the middle of the night, carrying a funeral urn of ashes? Diamond's somewhat illegal and highly secret break-in into the man's house only exposes increasingly awful information, and leads Diamond to a trail of uninvestigated deaths. As the man lingers on life support, Diamond must wrestle with the fact that he may have saved the life of a serial killer"--